2001
DOI: 10.1002/ajhb.1079
|View full text |Cite
|
Sign up to set email alerts
|

Marital status and age at natural menopause: Considering pheromonal influence

Abstract: Married women generally report a later mean age at menopause. The results reported here, from a study carried out in Greene County, New York, are no exception. Married and widowed women report a later mean age at natural menopause compared to single and divorced women (P < 0.05). To better understand the relationship between marital status and age at menopause, possible mechanistic and confounding variables are examined, in particular parity, sexual activity, smoking habits, level of education, and income. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 47 publications
(51 reference statements)
3
24
0
Order By: Relevance
“…Our findings from this study agree with previous researchers who have used different methodologies and studied different populations but arrived at similar conclusions, that married women generally attain menopause later when compared with never married or divorced women 9,18,[46][47][48] . It has been suggested that the effect of marriage on the attainment of menopause may be explained by biobehavioral factors such as sexual activity, parity and smoking habits, or even the pheromonal influence of the continued presence of a male in the household 46 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our findings from this study agree with previous researchers who have used different methodologies and studied different populations but arrived at similar conclusions, that married women generally attain menopause later when compared with never married or divorced women 9,18,[46][47][48] . It has been suggested that the effect of marriage on the attainment of menopause may be explained by biobehavioral factors such as sexual activity, parity and smoking habits, or even the pheromonal influence of the continued presence of a male in the household 46 .…”
Section: Discussionsupporting
confidence: 94%
“…However, other researchers say there is no relationship between mean age at menopause and level of education of the respondent 46 . Although the mechanism was not explored in this study, it is in fact possible for factors such as level of education and marital status to predict attainment of menopause among these women through their indirect influence on the recall and/or perception of menopause.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although many studies have reported associations between various socio-demographic, reproductive, or developmental factors and menopausal timing (for a general review, see Leidy Sievert, 2006), only a few are consistent predictors (reproductive characteristics, such as parity: Harlow and Signorello, 2000; marital status: Leidy Sievert et al, 2001;smoking: Parente et al, 2008). The inconsistency that characterizes many other associations may stem at least in part from methodological issues (Canavez et al, 2011;Harlow and Signorello, 2000), as accurate assessment of menopausal age can be difficult (Leidy Sievert, 2006;Leidy Sievert and Hautaniemi, 2003;Wood, 1994).…”
mentioning
confidence: 97%
“…In addition to variables that reflect childhood conditions, other factors associated with age at menopause that should be considered across the life course include parity (Cramer et al 1995;Gold et al 2001), cycle length (Kaczmarek and Szwed 2001;Whelan et al 1990), marital status (Sievert et al 2001); tobacco use (Cramer et al 1995;Gold et al 2001;Morris et al 2012;Reynolds and Obermeyer 2005), levels of education and socioeconomic status (Luoto et al 1994;Gold et al 2001;Mishra et al 2010;Shinberg 1998;Sievert and Hautaniemi 2003).…”
Section: Introductionmentioning
confidence: 99%